[P268] Monte Carlo study of photoneutrons from flattened filter free medical linear accelerator for BNCT applications. (August 2018) - Halato, Mohammed; Giannini, Gianrossano; Longo, Francesco; Artoli, A.; Alaamer, Abdulaziz; Suliman, Ibrahim
Abstract : Purpose: Studies in Italy have indicated the possibility of using photo-neutrons from high energy linac as a promising alternative neutron source to obtain intense neutron fluence rate for Boron Neutron Capture Therapy (BNCT) applications[1] . In continuation to these efforts, this study was carried out with aims: 1) to select high intensity linear accelerator that can be used for photo-neutron production; 2) to select the best materials for photo-neutron production. Methods: Initially, photon planner fluence and photons distributions have been simulated for a range of medical linear accelerators to study photon intensity using BEAMnrc Monte Carlo code. Due to its high photon intensity, The FFF Linac was selected as a nominal source to study photo-neutrons. Monte Carlo Simulations were then performed for photo-neutrons production from flattening filter free (FFF) medical Linac using lead and tungsten convertors. Results: Our results showed that photo-neutrons flux and yield increase with both photon energy and convertor thickness, saturating at 7 cm (lead) and 6 cm (tungsten) convertors. The average photoneutrons energy produced ranged from 0.480 to 0.863 MeV for the tungsten convertor and from 0.586 to 1.214 MeV for the lead convertor. A photoneutrons flux of 3.971 × 10 8 n/cm 2 s and 2.585 × 10 8 n/cm 2 s have been calculated for a 25 MeV medical linac equipped with 7 cm lead convertor and 6 cm tungsten convertor respectively. Conclusions: In conclusion the FFF linac presented a considerable feasibility toward having it as an alternative neutron source for BNCT with lead and tungsten as a suitable photoconverters.